2016
DOI: 10.1530/eje-15-1207
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Hypothalamic inflammation and nutrition

Abstract: Selected subpopulations of hypothalamic neurons play important roles in the regulation of whole body energy homeostasis. Studies have shown that the saturated fats present in large amounts in western diets can activate an inflammatory response in the hypothalamus, affecting the capacity of such neurons to respond appropriately to satiety and adipostatic signals. In the first part of this review, we will explore the mechanisms behind saturated fatty acid-induced hypothalamic dysfunction. Next, we will present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 82 publications
(148 reference statements)
1
25
0
5
Order By: Relevance
“…Considering the composition of juçara pulp, which is abundant in anthocyanins, MUFAs, and PUFAs, we postulated that the anti-inflammatory effect of juçara reaches CNS at low doses (0.25%). Our hypothesis is supported by the result of previous studies showing that the consumption of MUFAs and PUFAs can reverse hypothalamic inflammation [ 26 , 29 , 30 ]. Moreover, despite the lack of information regarding the effect of anthocyanins on the hypothalamus, studies demonstrating their positive effect on other tissues indicated that anthocyanins also have an anti-inflammatory activity in CNS [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…Considering the composition of juçara pulp, which is abundant in anthocyanins, MUFAs, and PUFAs, we postulated that the anti-inflammatory effect of juçara reaches CNS at low doses (0.25%). Our hypothesis is supported by the result of previous studies showing that the consumption of MUFAs and PUFAs can reverse hypothalamic inflammation [ 26 , 29 , 30 ]. Moreover, despite the lack of information regarding the effect of anthocyanins on the hypothalamus, studies demonstrating their positive effect on other tissues indicated that anthocyanins also have an anti-inflammatory activity in CNS [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the inhibition of hypothalamic FoxO1 expression in rats with diet-induced obesity improved insulin sensitivity, and reduced dietary intake, body mass, and insulinemia [21]. Thus, the role of MKP3 in this context is very important, because the hypothalamus is a key organ for the maintenance of energy homeostasis and FoxO1 deregulation occurs under conditions of metabolic syndrome, obesity and Type 2 diabetes mellitus (1)(2)(3).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothalamus acts as an important structure for metabolic control by regulating energy homeostasis through stimuli from the endocrine system [1][2][3][4]. In this context, insulin is an important regulator of energy homeostasis triggering a complex network of interactions between intracellular proteins [3].…”
Section: Introductionmentioning
confidence: 99%
“…The hypothalamus is the most important region of the brain capable of control food intake and energy expenditure. Thus, a better understanding of proteins involved in the hypothalamic control of energy homeostasis is necessary, once this mechanism is considered the pathophysiology of obesity (Araujo, Moraes, Cintra, & Velloso, ; Velloso & Schwartz, ). Herein, our results demonstrated that acute exercise session could modulate the APPL1 signaling and PI3K subunit, and reduce the food intake.…”
Section: Discussionmentioning
confidence: 99%